2002
DOI: 10.1148/rg.226025062
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of CT Findings in Acute Pyogenic Pelvic Inflammatory Disease

Abstract: Pelvic inflammatory disease (PID) is a common medical problem, affecting nearly 1 million women each year. Although the radiology literature is replete with discussions of the sonographic manifestations of PID, little has been published regarding the computed tomographic (CT) appearances of this entity. CT findings in early PID include obscuration of the normal pelvic floor fascial planes, thickening of the uterosacral ligaments, cervicitis, oophoritis, salpingitis, and accumulation of simple fluid in the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(69 citation statements)
references
References 7 publications
1
60
0
8
Order By: Relevance
“…Tuberculous TOAs usually mimic peritoneal carcinomatosis from ovarian cancers [4]. The rectosigmoid colon and ureter are the most common organs that can be involved by TOA [21][22][23]. Rectal involvement was present in our case, which contributed to the suspicion of malignancy.…”
Section: Discussionmentioning
confidence: 58%
“…Tuberculous TOAs usually mimic peritoneal carcinomatosis from ovarian cancers [4]. The rectosigmoid colon and ureter are the most common organs that can be involved by TOA [21][22][23]. Rectal involvement was present in our case, which contributed to the suspicion of malignancy.…”
Section: Discussionmentioning
confidence: 58%
“…In women with PID, perihepatitis associated with right upper abdominal pain is known as Fitz-HughCurtis syndrome (9,10). It has been demonstrated that hepatic capsular enhancement implying perihepatitis can be present in women with PID without right upper abdominal pain (9,11).…”
Section: Pelvic Inflammatory Diseasementioning
confidence: 99%
“…Giancarlo Schiappacasse F (1) , Eric Gana G (2) , M. Ignacia Ríos P (2) , Pablo Soffia S (1) . reportes cerca del 39% de las pacientes afectadas por EIP correspondían a ATO la cual ha aumentado especialmente en mujeres mayores de 40 años (6) .…”
Section: Infección Del Tracto Genital Superior Femenino: Revisión Picunclassified
“…Corresponde a la infección y la inflamación resultante del tracto superior de los órganos reproductivos femeninos, incluyendo el endometrio, las trompas de Falopio y los ovarios (2) . Reportes de la literatura estiman que es una de las enfermedades más comunes del género femenino afectando 1 millón de mujeres, representando 275.000 hospitalizaciones al año en EE.UU (3,4) .…”
Section: Introductionunclassified